POLA PEMAHAMAN KEAGAMAAN MASYARAKAT SIMPANG EMPATPASAMAN BARAT : STUDI TERHADAP ALIRAN HAQQUL YAQIN TAREKAT NAQSABANDIYAH - Siregar, Sawaluddin (Jurnal el-Qonuniy: Jurnal Ilmu-ilmu Kesyari'ahan dan Pranata Sosial, 2018)
HaqqulYaqin The Naqsabandiyah Order is one of the tarekat that developed in SimpangEmpatPasaman Barat, in spreading Sufistic teachings by using the method of remembrance as a form of ritual and its teachings. The purpose of the ritual activities carried out is to get mercy, pleasure, pleasure, get help in the world and the hereafter, get the advantages (supernatural powers and treatment) as well as the hope of efforts to achieve closeness with Allah as the ultimate goal.When considered HaqqulYaqin the Naqsabandiyah Congregation appears to have similarities with the muktabarahtarekat regarding basic teachings and practices and runs the Shari'a based on the Qur'an and Sunnah as well as the qaul ulama. But in some ways HaqqulYaqin the Naqsabandiyah Order is different from the muktabarahtarekat, for example the acceptance of new followers, wirid, training, tawajjuh, and tends to spiritual welfare or individual supernatural powers